Critical assessment of copyright and related rights' protection of publishers: Protection of commercial or cultural undertaking - Popović Dušan V. (Anali Pravnog Fakulteta u Beogradu)
In this paper the author discusses the legal policy reasons for the introduction of different forms of copyright and related rights' protection of publishers, existing in Serbian and comparative law: right of first publisher of previously unpublished work, publisher's right to a levy, right of publisher of critical and scientific publications, and right of online news publishers. It is argued in favour of a separate regulation of each of publisher's rights and pointed out to their different subject, content and object of protection. Although related rights of publishers are generally prescribed with a view to ensuring the protection of a commercial undertaking, the author also identifies certain reasons of cultural policy which led the legislator to provide for the legal protection of publishers of works already in public domain. Only the need to recompense the person who made available to the public a work which would otherwise remained practically unknown could justify such intervention into the public domain. Finally, it is concluded that the protection of online news producers in case of the making available of the parts of their media coverage by news aggregators could be seen as an instrument of protection against unfair competition.